Medicinal Effects of Mollugo cerviana - A Brief Review - A. A. Aglin (Current Aspects in Pharmaceutical Research and Development Vol. 7, 2022)
Over the past few years, human kind have been diagnosed with a wide range of infections and disorders. However, there are fewer effective allopathic drugs on the market. The increased knowledge in disease pathogenesis and bioactive components in last few years helps in the development of drugs. Based on knowledge from Ayurveda and Siddha practises, the immune system is supported in this scenario by using plant extracts. Mollugo cerviana is a phytochemical-rich herb that is available in India (commonly known as thread stem carpet weed). This plant is used to treat fever, stomach aches, jaundice, gout, and rheumatism. It is also used to encourage vaginal discharge following childbirth. The plant has antimicrobial, anti-inflammatory, antioxidant, and spermicidal properties. Because of the presence of phytochemicals such as carbohydrates, saponins, tannins, terpenoids, flavonoids, steroids, phenols, proteins, and alkaloids, the plant has hepatoprotective efficiency and photoprotective capacity in excess. In short, the plant extract is responsible for the majority of the medicinal applications. This review is a compilation of useful studies on Mollugo cerviana and its bioactivities.